Analisis Potensi dan Tantangan Pemanfaatan Artificial Intelligence (AI) dengan Metode Simple Additive Weighted (SAW) - Azhara, Muhamad Aldi; Quentara, Lilia Trisyathia; Subekti, Agus Topo (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Artificial Intelligence technology is becoming an essential component in education, especially for students, due to AI's potential to enhance learning efficiency, provide personalized solutions, and improve digital skills. However, AI utilization also presents challenges, such as over-reliance on technology and data privacy issues. This research aims to analyze the potential and challenges of AI implementation in the learning process among Industrial Engineering students. This study employs the Simple Additive Weighting (SAW) method to evaluate various criteria related to the benefits and challenges of using AI. Data were collected through questionnaires from 90 Industrial Engineering students at the Kalimantan Institute of Technology and The Indonesian institute OF technology & business. The results indicate that AI has significant potential in enhancing information access, task efficiency, and students’ overall learning experience. On the other hand, the main challenges faced by students include reliance on AI, reduced critical thinking skills, and concerns about data security and privacy.